Process for preparing wave-absorbing material by using lead-zinc smelting slag

By adopting the carbonization-magnetization process in the resource utilization of lead-zinc sludge, the problems of high pollution, high energy consumption and low resource utilization in the existing technology are solved, and the preparation of high-performance absorbing materials and efficient recovery of iron resources are achieved.

CN119685551APending Publication Date: 2025-03-25NORTHEASTERN UNIV CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411828497.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art has problems such as high pollution, high energy consumption and low resource utilization in the resource utilization of lead-zinc smelting slag, and traditional processes are difficult to effectively develop and utilize iron resources in lead-zinc smelting slag.

Method used

Using the carbonization-magnetization process, by mixing lead-zinc smelting slag powder with carbonization accelerator, carbon dioxide is introduced under heating and pressurization conditions for carbonization reaction, and then a mixed gas containing hydrogen is introduced into a high-temperature furnace for magnetization reduction and calcination, and finally a high-performance wave absorbing material is obtained through ball milling and magnetic separation.

Benefits of technology

It realizes the preparation of absorbent materials with high magnetic susceptibility, low impurities, energy-saving and environmentally friendly, improves iron recovery and material purity, and has a wide adaptability in the process, so it can effectively utilize complex lead and zinc slag raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005184968600000011
    Figure HDA0005184968600000011
  • Figure HDA0005184968600000012
    Figure HDA0005184968600000012
Patent Text Reader

Abstract

The invention relates to a process for preparing a wave-absorbing material by using lead-zinc smelting slag, which comprises the following specific steps: uniformly mixing lead-zinc smelting slag powder and a carbonization accelerator, introducing carbon dioxide under the conditions of heating and pressurizing to carry out carbonization reaction, and filtering and drying after the reaction is completed to obtain a carbonization reaction product; placing a carbonization reaction product obtained in the previous step into a high-temperature furnace filled with reducing gas for magnetization reduction roasting, and cooling to room temperature after the reaction is completed to obtain a magnetic material; and grinding and magnetically separating the obtained magnetic material to obtain the magnetic wave-absorbing material. The preparation process adopted by the invention has the advantages of energy-saving, efficient and environment-friendly process, low selectivity on raw material components, low impurity content of the product, good wave-absorbing performance, high metal recovery rate, no generation of carbon dioxide gas and the like, and overcomes the defects of narrow application range, high energy consumption, poor product performance, large carbon dioxide emission and the like in the existing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waste slag resource utilization, and in particular to a process for preparing an absorbing material by utilizing lead-zinc smelting slag. Background Art

[0002] The comprehensive utilization technology of lead-zinc smelting waste slag mainly includes pyrometallurgy, hydrometallurgy and combined smelting methods. Pyrometallurgy mainly includes rotary kiln method, namely Wiltz method, fuming method, Ausmelt method, Kifset method, vortex furnace and other methods; wet treatment adopts acid or alkaline leaching to recover the valuable metals. Domestic and foreign scholars have studied the 28d compressive strength of unburned ordinary bricks and blocks prepared with zinc smelting tailings as the main raw materials, which can reach more than 15MPa, but its cost is too high; there are also studies that use hydrothermal sulfidation to treat zinc-containing neutralized sludge, and then recover artificial sulfide ore by flotation to recover heavy metals, but its yield is low, pollution is large and the process is long. Lead-zinc smelting slag mainly contains iron oxides, lead-zinc oxides and silicates. The iron in lead-zinc smelting slag is mainly composed of strongly magnetic metallic iron, magnetic iron and weakly magnetic hematite, among which the iron content of weakly magnetic limonite accounts for about 66.30% of the total iron. The distribution of iron and zinc is relatively dispersed, and they are mutually wrapped with silicates, and the distribution is not concentrated, which makes mineral processing difficult. Patent 201810742166.9 uses a melt oxidation method to precipitate an unsaturated granular magnetite phase, and then grinds the magnetic material to prepare an absorbing material. However, this process uses air as an oxidant, which results in the inability to reduce the majority of limonite in the lead-zinc waste slag, the magnetic susceptibility of the smelting slag is low, and the resource recovery effect is greatly affected by the components of the smelting slag. In order to more effectively develop and utilize the iron resources in lead-zinc smelting slag, it is necessary to find a resource recovery process that is not limited by raw material conditions and has a wider range of adaptability. Summary of the invention

[0003] In view of the defects of high pollution, high energy consumption and low resource utilization rate in the process of resource utilization of lead-zinc smelting slag, the present invention provides a process for preparing absorbing materials using lead-zinc smelting slag. The preparation process adopted by the present invention has wide adaptability of raw materials, high magnetic susceptibility, energy saving and environmental protection, and the prepared absorbing materials have few impurities, good performance and high stability.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a process for preparing an absorbing material using lead-zinc smelting slag, characterized in that the preparation process comprises the following steps:

[0005] S1. Carbonization precipitation: The lead-zinc smelting slag powder and the carbonization accelerator are mixed evenly, and carbon dioxide is introduced under heating and pressurization conditions to carry out a carbonization reaction. After the reaction is completed, the carbonization reaction product is filtered and dried to obtain;

[0006] S2. Magnetization reduction: The carbonization reaction product obtained in step S1 is placed in a high-temperature furnace containing reducing gas for magnetization reduction roasting. After the reaction is completed, the temperature is cooled to room temperature to obtain a magnetic material.

[0007] S3. Ball milling and magnetic separation: Grind and magnetically separate the magnetic material obtained in step S2 to obtain a magnetic absorbing material.

[0008] The carbonization accelerator described in step S1 is one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, and ammonium carbonate aqueous solution with a concentration of 10-30%, and the solid-liquid mass ratio of lead-zinc smelting slag powder to the carbonization accelerator is 1:(1-10).

[0009] The carbonization reaction conditions described in step S1 are as follows: the partial pressure of the introduced carbon dioxide is 0.2-2.0 MPa, the reaction temperature is 80-200° C., and the reaction time is 0.5-5 h.

[0010] The high temperature furnace described in step S2 is one of a rotary kiln, a suspension roasting furnace, a molten pool smelting furnace and an electric furnace.

[0011] The reducing gas used in the magnetization reduction roasting in step S2 is a mixed gas of hydrogen and nitrogen, wherein the hydrogen concentration is 10-50%, and the mixed gas flow rate is 50-400 mL / min.

[0012] The magnetization reduction roasting conditions in step S2 are a reduction temperature of 450 to 950° C. and a reduction time of 0.5 to 3 hours.

[0013] The grinding conditions described in step S3 are a ball milling speed of 500 to 2000 rpm and a ball milling time of 0.1 to 1 h.

[0014] The magnetic separation conditions described in step S3 are a magnetic field strength of 800 to 2000 Oe and a magnetic separation time of 1 to 60 min.

[0015] Compared with the traditional method for preparing absorbing materials, the present invention has the following advantages:

[0016] 1. The present invention uses lead-zinc smelting slag as raw material for the first time, and obtains high-performance absorbing materials through a carbonization-magnetization method. The process is energy-saving and efficient, and the product has a low impurity content and a high metal recovery rate.

[0017] 2. The preparation process adopted by the present invention has low selectivity for raw material components and can utilize various types of lead-zinc slag raw materials with complex compositions.

[0018] 3. The carbonization step of the present invention completes the modification of the lead-zinc slag, forms lattice cracks and realizes the dissolution of other metals. The use of hydrogen as the magnetization reduction substance of the lead-zinc smelting slag can efficiently realize the reduction of iron in the cracks. The whole process can realize the separation of impurities in the lead-zinc smelting slag, low magnetization reduction temperature, high iron recovery rate and no generation of carbon dioxide gas, and the process is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solution of the product of the present invention, the following is a brief introduction to the drawings of the present invention. The drawings and the following specific embodiments are used to explain the present invention, but do not constitute a limitation of the present invention.

[0020] Figure 1 This is a SEM image of the absorbing material 1 prepared in Example 1 of the present invention.

[0021] Figure 2 This is an electromagnetic parameter diagram of the absorbing material 1 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0024] Example 1

[0025] Lead-zinc slag 1 was selected: the mass percentages of the components were 3.25% Na2O, 6.86% MgO, 6.23% Al2O3, 12.21% SiO2, 11.68% CaO, 1.38% MnO, 46.64% Fe2O3, 8.89% ZnO, and 2.86% other components.

[0026] Lead-zinc smelting slag powder and 30% sodium carbonate solution are mixed uniformly in a solid-liquid mass ratio of 1:1, 0.2MPa carbon dioxide is introduced under heating and pressurization conditions and the reaction temperature is maintained at 200°C for carbonization reaction for 0.5h. After the reaction is completed, the carbonization reaction product is filtered and dried to obtain the carbonization reaction product; the carbonization reaction product is placed in a rotary kiln, and 50mL / min of hydrogen and nitrogen mixed gas containing 50% hydrogen is introduced for magnetization reduction roasting, the reduction temperature is controlled at 950°C for reduction for 0.5h, and after the reaction is completed, it is cooled to room temperature to obtain a magnetic material; the obtained magnetic material is ground for 0.1h, the ball milling speed is controlled at 500rpm, and after grinding, it is subjected to magnetic separation for 1min under a magnetic field strength of 2000Oe to obtain an absorbing material 1.

[0027] Example 2

[0028] Lead-zinc slag 2 was selected: the mass percentages of the components were 7.42% MgO, 11.54% Al2O3, 33.76% SiO2, 15.78% CaO, 29.56% Fe2O3, 1.23% ZnO, and 0.71% other components.

[0029] The lead-zinc smelting slag powder and 10% potassium bicarbonate solution were mixed in a solid-liquid mass ratio of 1:10, and 2.0 MPa of carbon dioxide was introduced under heating and pressurization conditions and the reaction temperature was maintained at 80°C for carbonization reaction for 5 hours. After the reaction was completed, the carbonization reaction product was filtered and dried to obtain the carbonization reaction product; the carbonization reaction product was placed in a molten pool smelting furnace, and 400 mL / min of hydrogen and nitrogen mixed gas containing 10% hydrogen was introduced for magnetization reduction roasting, the reduction temperature was controlled at 450°C for reduction for 3 hours, and after the reaction was completed, it was cooled to room temperature to obtain a magnetic material; the obtained magnetic material was ground for 1 hour, the ball milling speed was controlled at 2000 rpm, and after grinding, it was subjected to magnetic separation for 60 minutes under a magnetic field strength of 800 Oe to obtain the absorbing material 2.

[0030] Example 3

[0031] Lead-zinc slag 3 was selected: the mass percentages of the components were 3.78% MgO, 12.98% Al2O3, 8.74% SiO2, 7.48% CaO, 42.97% Fe2O3, 21.0% SO3, 0.30% TiO2, 1.65% ZnO; and 1.10% other components.

[0032] The lead-zinc smelting slag powder and a mixed solution of sodium carbonate and ammonium carbonate with a concentration of 26.5% (the mass ratio of sodium carbonate and ammonium carbonate is 1:1) are uniformly mixed at a solid-liquid mass ratio of 1:6, and 1.6MPa of carbon dioxide is introduced under heating and pressurization conditions and the reaction temperature is maintained at 135°C for carbonization reaction for 3.7 hours. After the reaction is completed, the carbonization reaction product is filtered and dried to obtain the carbonization reaction product; the carbonization reaction product is placed in a molten pool smelting furnace, and 322mL / min of hydrogen and nitrogen mixed gas containing 23% hydrogen is introduced for magnetization reduction roasting, the reduction temperature is controlled at 525°C for reduction for 2.4 hours, and after the reaction is completed, it is cooled to room temperature to obtain a magnetic material; the obtained magnetic material is ground for 0.3h, the ball milling speed is controlled at 1512rpm, and after grinding, it is subjected to magnetic separation for 22min under a magnetic field strength of 1564Oe to obtain the absorbing material 3.

[0033] Example 4

[0034] Lead-zinc slag 4 was selected: the mass percentages of the components were 0.25% Na2O, 4.25% MgO, 12.88% Al2O3, 27.51% SiO2, 18.98% CaO, 1.18% PbO, 1.15% CuO, 6.01% SO3, 18.65% Fe2O3, 1.65% TiO2, 3.68% ZnO, and 3.81% other components.

[0035] Lead-zinc smelting slag powder and a 13% mixed solution of sodium bicarbonate, potassium bicarbonate and ammonium carbonate (the mass ratio of sodium bicarbonate, potassium bicarbonate and ammonium carbonate is 1:0.1:1.2) are uniformly mixed according to a solid-liquid mass ratio of 1:3.5, and 0.55MPa of carbon dioxide is introduced under heating and pressurization conditions and the reaction temperature is maintained at 97°C for carbonization reaction for 4.2 hours. After the reaction is completed, the carbonization reaction product is filtered and dried to obtain the carbonization reaction product; the carbonization reaction product is placed in a rotary kiln, and 233mL / min of a hydrogen and nitrogen mixed gas containing 46% hydrogen is introduced for magnetization reduction roasting, the reduction temperature is controlled to be 821°C for reduction for 1.1 hours, and after the reaction is completed, it is cooled to room temperature to obtain a magnetic material; the obtained magnetic material is ground for 0.3 hours, the ball milling speed is controlled at 952rpm, and after grinding, it is subjected to magnetic separation for 39 minutes under a magnetic field strength of 966Oe to obtain an absorbing material 4.

[0036] Example 5

[0037] Lead-zinc slag 5 was selected: the mass percentages of the components were 2.33% MgO, 10.30% Al2O3, 29.04% SiO2, 21.47% CaO, 1.97% SO3, 33.89% Fe2O3, and 1.00% other components.

[0038] The lead-zinc smelting slag powder and the potassium carbonate solution with a concentration of 15% were uniformly mixed at a solid-liquid mass ratio of 1:6.7, and 1.8 MPa of carbon dioxide was introduced under heating and pressurization conditions and the reaction temperature was maintained at 105°C for carbonization reaction for 1.9 hours. After the reaction was completed, the carbonization reaction product was filtered and dried to obtain the carbonization reaction product; the carbonization reaction product was placed in a rotary kiln, and 356 mL / min of hydrogen and nitrogen mixed gas containing 31% hydrogen was introduced for magnetization reduction roasting, and the reduction temperature was controlled to be 837°C for reduction for 0.9 hours. After the reaction was completed, it was cooled to room temperature to obtain a magnetic material; the obtained magnetic material was ground for 0.6 hours, and the ball milling speed was controlled at 1511 rpm. After grinding, it was subjected to magnetic separation for 23 minutes under a magnetic field strength of 1088 Oe to obtain the absorbing material 5.

[0039] The iron recovery rate and purity of the absorbing materials obtained in Examples 1 to 5 prepared above were tested and analyzed to evaluate their absorbing performance. The comparison material was a traditional commercial absorbing material. The analysis results are shown in Table 1 below. Figure 1 and Figure 2 The SEM image and electromagnetic parameter image of the absorbing material 1 prepared in Example 1 of the present invention are respectively illustrated. Figure 1 and Figure 2 It can be seen from the analysis results that although the lead-zinc slag compositions in different embodiments are quite different, the iron recovery rate and material purity are very high using the preparation process of the present invention, and the prepared absorbing material has good absorbing performance.

[0040] Table 1 Comparison of performance of prepared materials in different embodiments

[0041] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Materials Iron recovery rate 95% 92% 91% 93% 96% - Material purity 95% 93% 94% 94% 94% - Optimum reflection loss -38.6dB -36.6dB -35.3dB -32.7dB -32.5dB -15.9dB Effective absorption bandwidth 5.3GHz 4.7GHz 4.2GHz 4.5GHz 4.0GHz 2.6GHz

[0042] Finally, it should be noted that the above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A process for preparing an absorbing material using lead-zinc smelting slag, characterized in that: The preparation process comprises the following steps: S1. Carbonization precipitation: The lead-zinc smelting slag powder and the carbonization accelerator are mixed evenly, and carbon dioxide is introduced under heating and pressurization conditions to carry out a carbonization reaction. After the reaction is completed, the carbonization reaction product is filtered and dried to obtain; S2. Magnetization reduction: The carbonization reaction product obtained in step S1 is placed in a high-temperature furnace containing reducing gas for magnetization reduction roasting. After the reaction is completed, the temperature is cooled to room temperature to obtain a magnetic material. S3. Ball milling and magnetic separation: Grind and magnetically separate the magnetic material obtained in step S2 to obtain a magnetic absorbing material.

2. A process for preparing an absorbing material using lead-zinc smelting slag as claimed in claim 1, characterized in that: The carbonization accelerator described in step S1 is one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, and ammonium carbonate aqueous solution with a concentration of 10-30%, and the solid-liquid mass ratio of lead-zinc smelting slag powder to the carbonization accelerator is 1:(1-10).

3. The process for preparing an absorbing material using lead-zinc smelting slag according to claim 1, characterized in that: The carbonization reaction conditions described in step S1 are as follows: the partial pressure of the introduced carbon dioxide is 0.2-2.0 MPa, the reaction temperature is 80-200° C., and the reaction time is 0.5-5 h.

4. The process for preparing an absorbing material using lead-zinc smelting slag according to claim 1, characterized in that: The high temperature furnace described in step S2 is one of a rotary kiln, a suspension roasting furnace, a molten pool smelting furnace and an electric furnace.

5. The process for preparing an absorbing material using lead-zinc smelting slag according to claim 1, characterized in that: The reducing gas used in the magnetization reduction roasting in step S2 is a mixed gas of hydrogen and nitrogen, wherein the hydrogen concentration is 10-50%, and the mixed gas flow rate is 50-400 mL / min.

6. The process for preparing an absorbing material using lead-zinc smelting slag according to claim 1, characterized in that: The magnetization reduction roasting conditions in step S2 are a reduction temperature of 450 to 950° C. and a reduction time of 0.5 to 3 hours.

7. The process for preparing an absorbing material using lead-zinc smelting slag according to claim 1, characterized in that: The grinding conditions described in step S3 are a ball milling speed of 500 to 2000 rpm and a ball milling time of 0.1 to 1 h.

8. The process for preparing an absorbing material using lead-zinc smelting slag according to claim 1, characterized in that: The magnetic separation conditions described in step S3 are a magnetic field strength of 800 to 2000 Oe and a magnetic separation time of 1 to 60 min.

Citation Information

Patent Citations

  • Method for preparing wave absorption material from lead zinc slag and wave absorption material

    CN108690557A